Digital Business Innovation Using the Quintuple Helix Model - Samrotul Fuadah, Salsa aura; Fithri Widyanita Yarisma; Pradifaliani Nurhidayati (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
In the era of Society 5.0, where digital technology is an inseparable part of the lives of the younger generation, they are encouraged to innovate and create new things, especially in the field of digital business which is in great demand. This research explores Quintuple Helix’s concept, which involves academics, industry, government, society, and nature to encourage digital business innovation. The descriptive qualitative method was chosen using secondary data from various sources, such as books, articles, home pages to access information data relevant to the Quintuple Helix collaboration concept. Quintuple Helix, can help the younger generation in improving their ability to innovate and adapt in the digital era, develop creative and sustainable new business models, and provide innovative solutions to answer the challenges and needs of society.